MESC (Marginal Effective Statutory Charge), an extension of King-Fullerton methodology - Marcel Gérard; Laurence Beauchot; Sylvie Jamaels; Christian Valenduc (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
The purpose of this paper is twofold. On the one hand it aims at extending King-Fullerton methodology to a larger scope of liabilities and primarily, in the empirical section of the paper, to statutory charges associated to labour costs, basically employers' contributions to social security. Thus it proposes substituting MESC or Marginal Effective Statutory Charge, for King-Fullerton METR, and enlarging the p-statistics to requirements in terms of labour cost coverage, then reinterpreting it in terms of marginal value added. A further extension to environmental levies as well as a generalisation to any market failure inefficiency loss are also presented. On the other hand the paper intends to emphasize the key role of factor supply elasticities or relative mobility and market rigidities in determining the impact of the - or part of the - MESC statistics on the location decision of an MNE, a Multinational Enterprise. Indeed, in a setting where no rigidities are at work on the market for the immobile factor, like labour, levies on the compensation of that factor don't matter for MNE decision. Unlike that, in a setting where such rigidities are present, they do matter since they refrain the possibility to pass the burden of the tax on the holder of the rather immobile factor. The ultimate goal of the paper is, through the topics mentioned above, to cope with issues especially relevant for interjurisdictional behaviour of multinational entreprises without the framework of a nex Federation like the European Union.
Keywords: 330; Marginal Effective Tax Rate; Excess Burden; Optimal Taxation; Corporate location decision; Unternehmensbesteuerung; Personalzusatzkosten; Steuerbelastung; Excess Burden; Betriebliche Standortwahl; Standortwettbewerb; Schätzung; Theorie; EU-Staaten